Efficacy of endometrial aspiration cytology in diagnosis of endometrial pathologies in a tertiary care centre - Samruddhi S Thakare; Dhiraj B Nikumbh; Nandkumar V Dravid; Rajshri P Damle; Prashant N Deore (International Journal of Health and Clinical Research, 2022)
Introduction: Endometrial pathologies contribute significantly to increased morbidity and mortality in females, and still tend to remain undiagnosed till later stages. Endometrial cytology is one of the most powerful and reliable investigations in detection of various endometrial pathologies, including hyperplasia, malignancies and can be used as an early evaluative modality on routine basis. Objectives: The present study was aimed at assessing the diagnostic efficacy of endometrial aspirate cytology in the diagnosis of various endometrial pathologies in terms of accuracy, sensitivity and specificity etc., considering histopathology as standard . It also involved the study of various morphological patterns ranging across the spectrum of endometrial pathology by aspiration cytology . Material and methods: Using Karmann’s cannula, endometrial aspirate sample was obtained in 106 patients from gynaecology out-patient department and the smears were stained using papanicolaou stain. The findings of cytology were correlated with histopathology. Results: The present study comprises 106 patients. 102 out of 106 samples for cytology were adequate with an overall diagnostic accuracy of 95.1% , a sensitivity of 93.2%, specificity of 97.7%, with 98.2% positive predictive value and 91.3% negative predictive value. Conclusion: Endometrial aspiration cytology is an easy to perform, minimally invasive, safe and cheaper procedure for diagnosing endometrial pathologies. Its results are fairly acceptable with good cyto-histopathological correlation and hence can be used for screening of endometrial pathologies and malignancies.